Dead food, the political economy of disease and climate injustice: Cynical reasonand decolonial feminist bioethics - Arguedas Ramírez, Gabriela (2025)
In this article, the author argues that unchecked political power held by big corporations is one of the most important factors driving the proliferation of in effective public policies against hunger and climate change. One of the most pressing ethical issues, that currently receives little attention in bioethics, is the normalization of tolerance toward structural injustice in institutions and organizations that have the responsibility of leading the way in the global fight to eradicate hunger and confront climate change. This cultural, ethical, and political issue can be better understood as part of what the author has conceptualized as institutionalized cynical reason.